امام غزالیؒ اور علامہ ابن خلدونؒ کے نظریہ تعلیم وتربیت کا تقابلی جائزہ (Contemporary Journal of Social Science Review, 2025)
This study presents a comparative analysis of the educational theories of two eminent Islamic thinkers within the framework of Imam Abu Hamid al-Ghazali's Ihya Ulum al-Din and Abd al-Rahman Ibn e Khaldun's Al-Muqaddimah. Imam al-Ghazali defined the fundamental aim of education as the spiritual purification of the individual, moral refinement, and attaining closeness to Allah Almighty. In his view, knowledge is not merely an intellectual activity but a means for the purification of the soul. In contrast, Ibn e Khaldun links education to civilizational development, societal needs, intellectual growth, and social evolution. For him, the educational process is shaped by mental habits, experiences, and the social environment.This research undertakes a comparative analysis of both thinkers' perspectives on the definition of knowledge, the objectives of education, curriculum priorities, educational principles, the relationship between teacher and student, and social impacts. The study reveals that while al-Ghazali's approach focuses on spiritual, ethical, and inner development, Ibn e Khaldun's viewpoint is grounded in empirical, observational, and sociological principles. Consequently, this paper elucidates the comprehensive breadth of Islamic educational thought, which is not confined solely to spiritual or social dimensions but represents an integrated system for the holistic development of the human personality, harmonizing ethics, intellect, society, and spiritual training.